AGE ESTIMATION USING DEVELOPMENT OF THIRD MOLARS IN 14- 24 YEARS AGE GROUP: A RADIOLOGICAL STUDY (Journal of Forensic Medicine & Toxicology, 2023)
Background: Age estimation is important not only for identifying unknown dead bodies in the context of criminal situations or mass disasters but also for living individuals in medico-legal such as rape, child labor, child marriage, sports and accidents in cases of legal immigrants. Material and Methods: This cross-sectional prospective study was conducted in the Department of Forensic Medicine and Toxicology, in association with Radiology Department, S.P. Medical College, Bikaner (Rajasthan) after taking Institutional ethics committee approval to conduct the study. The study comprised of 136 randomly selected subjects age ranging from 14 to 24 years. High quality Orthopantomogram (OPG) radiographs were taken after taking informed consent. Results: Mean age of all developmental stages (A- H) is lower in males as compared to females but difference is statistically insignificant. Individuals with third molars at the G and H stages are likely above 18 years while those at D, E and F are likely below 18 years. Conclusion: Tooth is one of the few predictors available for the assessment of age in the 16– 23 year age group and root maturity in the third molar may be one marker that indicates an individual is at least 18 years of age.
Keywords: Third molar tooth; Age estimation; Chronological age; forensic dentistry